The Effect of Carbon Emissions (CO2) on Financial Development, Capital Formation and Economic Growth in Nigeria - Yusuf Shamsuddeen Nadabo (International Journal of Advanced Technology and Social Sciences, 2023)
This study investigates the influence of carbon emissions (CO2) on financial development, capital formation, and economic growth in Nigeria. Using the ARDL model and the Toda-Yamamoto causality test from 1991 to 2021, the study finds a positive and significant relationship between economic growth and carbon emissions in the short run. However, in the long run, this relationship becomes negative and significant. Domestic credit to the private sector has a positive and significant impact on economic growth in both the short and long run. Gross fixed capital formation has a negative and significant impact on economic growth in the short run, but a positive and significant impact in the long run. Trade openness also has a positive and significant impact on economic growth in both the short and long run.  The Toda-Yamamoto causality results reveal a one-way relationship between economic growth and CO2 emissions. These findings have important policy implications governments should prioritize sustainable development and carbon emissions reduction by investing in renewable energy, improving energy efficiency, and promoting sustainable transportation. Additionally, governments should invest in human capital